A queerly joyful noise : choral musicking for social justice - Balen, Julia, 1955- (Rutgers University Press, 2017)
A Queerly Joyful Noise investigates why so many LGBTIQ people are drawn to choral music and how queer chorus members create an experience that is beautiful and politically impactful. Julia ""Jules"" Bal#65533;n vividly conveys how queer choruses can collectively empower their singers and serve as progressive rallying calls for their listeners.